Effect of Persulphate Pretreatment on the Formation of Chlorinated Phenolic Compounds - Prakash, Divya Prakash; Malhotra, Rachna; Kumar, Satish (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Estimation of different chlorophenolic compounds formed during CEH bleaching of oxygen and persulphate-peroxide pretreated wheat straw soda pulp has been carried out. The results have been compared with CEH bleaching without any pretreatment. The results show that CEH effluent is toxic in nature as it contains many chlorophenolic compounds with concentration exceeding the 96LC50 values. Results indicate that chlorocatechols are predominant in CEH, cholorosyringaldehydes in (PxP)CEH and chlorophenols in OCEH bleaching effluents. The results further indicate that persulphate-peroxide pretreatment reduces the amount of chlorinated phenolics formed by 36% to 109.9g/t and the number of identified chlorophenolics to 24 from 26 in CEH. Oxygen pretreatment reduces the amount of chlorinated phenolics by 86% to 22.8 g/t and the number of chlorophenolics to 14 thereby reducing the toxicity of the effluent.